2022
DOI: 10.1073/pnas.2202469119
|View full text |Cite
|
Sign up to set email alerts
|

Cip1 tunes cell cycle arrest duration upon calcineurin activation

Abstract: Significance To ensure their survival, cells arrest the cell division cycle when they are exposed to environmental stress. The duration of this arrest is dependent upon the time it takes a cell to adapt to a particular environment. How cells adjust the amount of time they remain arrested is not known. This study investigates the role of the phosphatase calcineurin in controlling cell cycle arrest duration in yeast. We show that calcineurin lengthens arrest by prolonging Hog1-dependent activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…To better understand the response to chronic stress, we monitored CN activity as cells grew in CaCl2 for 72 hours using a fluorescent reporter (CNR-C), which measures CN-dependent dephosphorylation and nuclear localization of a GFP-tagged, non-functional fragment of Crz1. Consistent with previous studies (Stathopoulos-Gerontides et al, 1999;Leech et al, 2020;Flynn and Benanti, 2022), we observed CN-dependent changes in CNR-C within 10 minutes of CaCl2 treatment and both wild-type and crz1D cells initially activated CN to similar extents, as shown by the rapid appearance of the higher mobility CNR-C species and increased nuclear signal (Figure 2, A and B). In wild-type cells, CN was inactivated within 3 hours after CaCl2 treatment as indicated by the reappearance of the phosphorylated, lower mobility CNR-C species and loss of nuclear signal (Figure 2, A and B).…”
Section: Crz1 Is Required To Inactivate Cnsupporting
confidence: 92%
See 3 more Smart Citations
“…To better understand the response to chronic stress, we monitored CN activity as cells grew in CaCl2 for 72 hours using a fluorescent reporter (CNR-C), which measures CN-dependent dephosphorylation and nuclear localization of a GFP-tagged, non-functional fragment of Crz1. Consistent with previous studies (Stathopoulos-Gerontides et al, 1999;Leech et al, 2020;Flynn and Benanti, 2022), we observed CN-dependent changes in CNR-C within 10 minutes of CaCl2 treatment and both wild-type and crz1D cells initially activated CN to similar extents, as shown by the rapid appearance of the higher mobility CNR-C species and increased nuclear signal (Figure 2, A and B). In wild-type cells, CN was inactivated within 3 hours after CaCl2 treatment as indicated by the reappearance of the phosphorylated, lower mobility CNR-C species and loss of nuclear signal (Figure 2, A and B).…”
Section: Crz1 Is Required To Inactivate Cnsupporting
confidence: 92%
“…CN is strongly activated within minutes of exposure to CaCl 2 and is subsequently inactivated as cells adapt (Stathopoulos-Gerontides et al ., 1999; Leech et al ., 2020; Flynn and Benanti, 2022). However, the timing of CN inactivation and adaptation during prolonged stress exposure is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations